Knowledge transfer, power and empowerment: MNCs’ transfer of vocational education and training to their international subsidiaries - Fuchs, Martina (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
International knowledge transfer in multinational companies (MNCs) is a key issue in economic geography. However, until now the debate has largely neglected the question if knowledge transfer empowers the international partners and thus enables and encourages them in self-determined acting and thinking within their social contexts. This contribution focusses on empowering strategies of those who transfer the knowledge. The empirical study concentrates on training managers and trainers in German MNCs, who transfer vocational education and training to locations in China and India. The study follows a qualitative methodological approach and is based on comprehensive expert interviews. The results show that the training managers and trainers of vocational education and training ambitiously engage in empowering the apprentices in the subsidiaries. However, there are local frictions. Thus, the training managers and trainers generate ‘power to empower’ the apprentices. Their success is limited, as the paper illustrates.